The Role of Accountants in Achieving Sustainable Development Goals: Academics Perspective - Firmansyah, Irman (Jurnal Ilmiah Akuntansi dan Bisnis; Vol 14 No 2 (2019), 2019)
ABSTRACT This study aims to provide a general description of the role of accountants on sustainable development goals achievement. A qualitative- quantitative research method was used in the analytic network process. The results showed that the role of accountants in achieving the sustainable development goals is divided into three dimensions. The first is the role of the accounting professional organization in providing input to the government about SDGs. The second role of professional accountants is that an accountant must provide SDGs elemental messages in providing recommendations on financial statements. The third role is as an educator; an accountant compiles an education curriculum that adapts to the goals of the SDGs. Keywords: Accountants; sustainable development goals; academics